WASHING TEST OF KENDILO COAL USING A SINK-FLOAT METHOD TO IMPROVE ITS QUALITY - Wanda Adinugraha; Nana Sulaksana; Hendarmawan Hendarmawan; Binarko Santoso; Datin Fatia Umar; Fitri Amalia (Indonesian Mining Journal, 2018)
Kendilo coal is known as a high-ash content type. Beneficiating such the coal for gasification process needs to wash the coal first. The purpose of washing is to lower the ash content until the permitted amount of about 10%. Samples for coal washing were obtained from PT. Kendilo Coal Indonesia at Pasir Belengkong, Paser Regency, East  Kalimantan. The samples were taken at Bindu and Betitit Block, which containing ash of about 20%–30%. To wash the coal samples, a sink-float method was applied to test its separation characteristic. The washing process employed three sizes fraction, i.e, -12.5+5.6, -5.6+1.18, and -1.18 mm and the separation density was varied between 1.3 to 1.6 g/cc within the interval of 0.1. The liquid solutions as the separation media were made from mixing of perchloroethylene and toluene. From the coal washability curve, the best coal washing in order containing ash content of about 8% in the case of Bindu Block's coal, occurs at the fraction of -12.5+5.6 mm, at density separator of 1.36 g/cc with the recovery of 50%. While the coal of Betitit's Block, the washed coal was 50.82% at similar fraction but at different density separator of 1.39 g/cc.